Strategies For Increasing The Welfare Of Oil Palm Farmers Through The Acceleration Of The Term Of Change Program In Tanjung Jabung Timur Regency - Rita Andriana, Anggia; Kholis, Muhammad; Arifa’illah Syaiful Huda, Imam (Sustainability (STPP) Theory, Practice and Policy, 2022)
The purpose of this study, namely 1). to determine the level of knowledge of oil palm farmers on the improvement program, 2). How is the willingness of oil palm farmers to participate in the Benah Term Strategy program, 3). the hope of oil palm farmers in the improvement program. This research was designed with qualitative research with a grounded theory approach. The number of informants in this study were 10 people. The technique of determining informants uses the snowball technique. The results showed that there were still many oil palm farmers who did not know about the clean-up program, but after being explained by the researchers regarding the clean-up term program, the oil palm farmers strongly agreed to participate in the clean-up activity. The results showed that there were still many oil palm farmers who did not know about the clean-up program, but after being explained by the researchers regarding the clean-up term program, the oil palm farmers strongly agreed to participate in the clean-up activity. up program. It is the hope of oil palm farmers that this clean-up program can be an additional support for the family's economy and preserve the environment.